Contextualizing corporate control in the agrifood and extractive sectors - Jennifer Clapp; Joseph Purugganan (Globalizations, 2020)
Corporations have gained enormous power and influence in recent decades as mergers and acquisitions in just about every sector of the global economy have given rise to mega-sized companies that influence almost every aspect of our lives. In this contribution, we examine the rise of corporate concentration and control in two key sectors – agriculture and extractives – where in recent years consolidation has accelerated due to a combination of technological change, weakening state regulation and financial pressures, leaving these sectors largely controlled by just a handful of giant players. Corporate concentration and control in these sectors has important consequences, contributing to heightened inequality, environmental harm, and human rights violations. This paper reflects on the strategies of civil society and social movements in contesting extreme consolidation and corporate power. It calls for a multiscale approach that restores the regulatory powers of states and reestablishes people's sovereignty on a broader scale.